THE HONORIFICS EXPRESSIONS IN INDIGENOUS LANGUAGE OF JAVA ISLAND ETHNICS WITH RELEVANCE INTO ENGLISH - Zaman, Mochamad Nuruz; Nababan, Mangatur Rudolf; Djatmika, Djatmika (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2018)
This research is a sociolinguistics study by examining greetings and verbs that accommodate honorific expressions in addressee, referent, bystander, and entire honorifics categories. This study also focuses on novel drama genre and women's struggle in upholding justice by Okky Madasari, Entrok, 86, Maryam, Pasung Jiwa, and Kerumunan Terakhir. The used descriptive qualitative method is analysis model of Spradley known as ethnography methodology that is highly domain analysis of data sources. Addressee honorifics well integrates into all kinds of them; they are in a kinship of family and relative, second personal pronoun, non-kinship of general society, occupational, religion, and local custom, as well as a verb.Furthermore, referent honorifics develops in almost kinds of them, and they are kinship of family, second personal pronoun, non-kinship of general society, occupational, religion, and local custom, as well as a verb. While by-stander honorifics flies in a half part of them, they are kinship of relative, third personal pronoun, non-kinship of general society, occupational, religion, and local custom. However, absolute honorifics consistently synergies with one part of them, it is religion.